A high capacity chopper for water hyacinth - Alam, Murshed; Gee-Clough, D.; Gupta, Chandra P.; Cochran, Billy J.; The Government of Australia (Bangkok : Asian Institute of Technology, 1985)
A high capacity chopper was designed, fabricated, tested and evaluated for chopping of water hyacinth. The chopper was designed with twenty seven circular saw blades of 254 mm diameter and those were fixed on two shafts which were rotating at different speeds and in opposite directions. The gap between two adjacent saws gradually increased from 26 mm to 57 mm and overlapping of saws from the two shafts was 64 mm. Two arrangements of chopper were tested: water hyacinth feeding in a vertical and in a horizontal direction for finding the best chopping. Chopping tests were conducted at different chopper speeds with an individual plant of different mass. Peak power requirements were measured for chopping. A floating teat was conducted to measure the degree of comminution of the chopped materials. Regression analysis of the total peak power requirements of two components for cutting a plant of water hyacinth was done. The two components were: (1) Total power requirement for operating the chopper at no-load condition. (2) Peak power required for cutting a plant. The total power requirement for operating the chopper at no load condition consists of: (a) Power for operating the chopper motor. (b) Power losses from belt slippages, chopper shaft frictions and windage. The machine offered a very good capacity, 25 metric tons/hour of 31.25 metric tons/hour/meter of conveyor width at 120 RPM of conveyor speed. The peak power consumption in chopping was 3.98 kw with equivalent amount of energy of 0.159 kw-hr/t (0.574 MJ/t). However, there were some constraints in the experiment. Further testing of the chopper with harvester is required under field conditions.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Hyacinths; Forage harvesting machinery